1993
DOI: 10.1111/j.1600-0528.1993.tb00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived need and use of oral health services among adolescents and adults in Tanzania

Abstract: The perceived need and use of oral health services among adolescents and adults in Tanzania were studied. One region from each of the country's five zones was chosen at random. Final sample selection (n = 1061) was done in the main towns of the selected regions. Participants were interviewed using a structured questionnaire which dealt with perceived need for dental treatment and use of oral health services and several demographic variables. Frequency tables were computed and analyzed. Odds ratios were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 11 publications
5
29
0
Order By: Relevance
“…One study showed that self-perception was greater among those who had not used dental services, 4 while others showed it was greater among those who had. 3,9,16 In the present investigation, an association was found in univariate analysis that did not persist in multivariate analysis.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…One study showed that self-perception was greater among those who had not used dental services, 4 while others showed it was greater among those who had. 3,9,16 In the present investigation, an association was found in univariate analysis that did not persist in multivariate analysis.…”
Section: Discussionsupporting
confidence: 50%
“…asking whether the interviewees did or did not have a need for dental treatment. Other authors 16,23 have asked about the existence of any dental problems or have constructed variables that combined the need for treatment with the existence of signs and symptoms of diseases. In an investigation conducted among elderly people in Florida (United States), 11 the variable was constructed from the following questions: "Do you think you need any dental care today or over the next 14 days?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that women have better oral health behaviour than men (12,13). Women brush their teeth 4 times more than men (11), while others (14) found no differences in brushing frequency between genders.…”
Section: Introductionmentioning
confidence: 99%
“…[22] The most common oral care carried out in public dental clinics is tooth extractions. [23][24][25] Additionally, the limited number of dental clinics that offer restorative care in Tanzania has been as an obstacle towards accessing restorative services when needed. [24,25] There are other barriers to restorative services including shortage of equipment, lack of funds to purchase materials and dental materials not being available.…”
Section: Dental Care In Tanzaniamentioning
confidence: 99%